2022
DOI: 10.1080/21655979.2022.2051839
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated long intergenic non-protein coding RNA 1094 (LINC01094) is linked to poor prognosis and alteration of cell function in colorectal cancer

Abstract: Colorectal cancer (CRC) showed high cancer-related mortality in recent years partly due to the absence of an effective prognostic predictor. This research intended to evaluate the prognostic value and potential role of long intergenic non-protein coding RNA 1094 (LINC01094) in CRC. In this work, we evaluated the LINC01094 level in 122 CRC patients’ tissues and in human CRC cell lines. We explored the ability of LINC01094 in overall survival and progression-free survival estimate. The effect of LINC01094 dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In colorectal cancer, LINC01094 was also highly expressed and correlated with lymph node metastasis and TNM stage. LINC01094 promoted proliferation, invasion, and migration of colorectal cancer cells by sponging miR-1266-5p (Zhang et al, 2022). Thus LINC01094 is an oncogene in an array of tumors.…”
Section: Discussionmentioning
confidence: 94%
“…In colorectal cancer, LINC01094 was also highly expressed and correlated with lymph node metastasis and TNM stage. LINC01094 promoted proliferation, invasion, and migration of colorectal cancer cells by sponging miR-1266-5p (Zhang et al, 2022). Thus LINC01094 is an oncogene in an array of tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Xu et al reported that the lncRNA UBE2R2-AS1 targeted the miR-877-3p/TLR4 axis, thereby promoting apoptosis in glioma cells ( Xu et al, 2021 ). In colorectal cancer, upregulated long intergenic non-protein-coding RNA 1094 (LINC01094) is associated with a dismal prognosis and altered cellular function ( Zhang et al, 2022 ). The RBAKDN gene has been linked to the prognosis of patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01094 was identi ed to be overexpressed in many different types of cancerous tissue, most notably glioblastoma, lung adenocarcinoma, and colorectal cancer (32)(33)(34). Poor prognosis is related with high LINC01094 expression in gastric cancer, and this may be due to its association with the epithelialmesenchymal transition pathway and macrophage in ltration (35,36).…”
Section: Discussionmentioning
confidence: 99%